“Expletives” as Discourse Markers: Semantic and Pragmatic Considerations in “It” and “There” - Dr. Amjad Ali (University of Chitral Journal of Linguistics and Literature, 2023)
This paper explores the syntactic and semantic configurations of expletives “it” and “there.” It attempts to show that expletives are not just syntactic fillers; they are semantic markers and are pragmatically bound NPs that can be co-indexed with covert referents. The study follows a theoretical approach and applies Bolinger’s (1977) Meaning and Form model to the syntactic configurations of expletives. The syntactic structures of expletives are based on the syntactic theories of generativist linguists, namely Chomsky (1986). Chomskyan syntactic theories describe the various formal characteristics of expletives without analyzing their semantic and pragmatic implications. This study premises that Bolinger’s theoretical modal can fill these missing gaps and can provide a conclusive yet not final description of these gaps. The study recognizes expletives as discourse bound markers and authenticates their contextual and sociological significance.